Cartographic aspects of the theater performances Odisseia 116 and BR3 (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article is an analysis of the writing process of the dramaturgy Odisseia 116 based on a six-day trip by bus between Rio de Janeiro and Ceará. Dramaturgy is structured on a triad: autobiographical characteristics; the possibility of interviewing people and photographing traveling landscapes and the Homeric Odyssey, the inspiring work of this writing. A cartography emerges as a methodology from the trip and consolidates itself in dramaturgy. Dialogue with interviews given by Antônio Araújo and Bernardo Carvalho about the BR3 show. In the final considerations, I point to three possible cartographies: the travel cartography, the dramaturgy cartography and the rehearsal room cartography.
Keywords: Travel; Dramaturgy; Cartography